Pengaruh Tingkat Pendidikan Orang Tua Terhadap Tingkat Kecerdasan dan Keaktifan Siswa dari Kelas Satu Sampai dengan Kelas Enam Pada Semester I: The Influence of Parents' Education Level on the Level of Intelligence and Activeness of Students from Grade One to Grade Six in Semester I - Sunain, Sunain (Pedagogia : Jurnal Pendidikan, 2017)
This study aims to determine (1) the effect of parental background education on student learning outcomes, (2) the influence of the level of parental education background with student learning activities. Data collection and documents using 120 questionnaires from students and with descriptive analysis and quantitative techniques. The result of this study also is (1) there is showed significant influence between positive and high parent education background of student learning result with r value 75,5%; (2) there is influence between parent attention with educational background to student learning activity with value r 78.0%.